Peran Tenaga Kerja Asing China Pada Proyek Smelter di Indonesia Pada Tahun 2018-2021 - Qothrunnada Qothrunnada; Reni Windiani; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2022)
One of the national strategy projects being intensified in Indonesia is the smelter project. The smelter project still requires workers from outside, namely Chinese foreign workers. The arrival of Chinese foreign workers to Indonesia has always been a sensitive issue. There are still many people who question the interests of the Chinese foreign workers. This study aims to find out more about the mobility and role of Chinese foreign workers in the PT Halmahera Persada Lygend smelter project. In an effort to answer this research using the concept of Globalization from Jagdish Bhagwati. This study uses a qualitative method. The results of this study show that the qualifications of Chinese foreign workers are indeed considered capable because the smelter project is a strategic project that is still a new thing in Indonesia so that it requires a workforce that is capable and has experience. This job opportunity can be given to anyone but back again to anyone who is ready and has the capability. The author's suggestions for the future can show the transformation of globalization that has occurred in the smelter project.